STUDI PERENCANAAN SARANA PENYEDIAAN AIR BERSIH PERDESAAAN DESA SIDOREJO KEC. DOKO, KAB.BLITAR - Yuris Permana Yoga Utama (PROGRAM STUDI TEKNIK SIPIL FAKULTAS TEKNIK UNIVERSITAS TULUNGAGUNG, 2021)
Abstract Sidorejo Village is one of the villages located in Doko District which is in the northeast of the capital city of Blitar Regency - Kanigoro with a distance of about 27.8 Km. The topography of the northern part of the region is hilly, mountainous and prone to natural disasters, Indonesian soil and flooding. The population of Sidorejo Village in 2018 was 4,828 people. This village is a surplus area because of its fertile soil, due to volcanic ash from the volcano so that many plants grow well. The regional mainstay potential is in agriculture and horticulture while the regional mainstay commodities are rice, corn, and cassava. At this time, the residents of Sidorejo village use clean water from village water sources and do not yet have adequate clean water services. Due to the inadequate flow of drinking water from village water sources, it is often problematic to carry moss and mud and sometimes the network is cut off due to landslides, the residents of Sidorejo village decided to make a proper clean water supply facility to overcome the problem of clean water in their village. This study aims to determine the need for clean water in Sidorejo village, to know the planning of the pipeline network and to know the required budget plan. According to field conditions and regional topography, the drinking water network is channeled using a gravity system consisting of a water catchment tank, bronkaptering system, to the transmission pipe. The catch basin is designed to surround a raw water source with a width of 3.70 meters and a length of 1.87 meters which serves to accommodate temporary source water. The bronkaptering is built with dimensions of 3.40 m wide and 2 m high. It is equipped with a simple filter system to maintain the quality of drinking water before it is sent to the transmission pipe. The transmission network from broncaptering is multiplied using a 96 meter long GI dia 3 pipe and a 12.5 meter PVC (RRJ) pipe 1,920 meters long with thrust block every 9 meter. The Budget Plan (RAB) needed in planning the clean water supply facilities in Sidorejo Village, Doko District as a whole is Rp. 189.089.000, - (One Hundred Eighty Million Eighty Nine Rupiah) including VAT. Keyword: cIean water netw0rk, water catchment tank, broncaptering, simple filter system, gravity system, the transmission pipe, thrust block, the budget plan. Abstrak. Desa Sidorejo meupakan salah satu desa yang terletak di Kecamatan Doko yang berada di timur laut Ibu Kota Kabupaten Blitar - Kanigoro dengan jarak sekitar 27,8 Km. T0p0grafi wiIayah BIitar di bagian Utara ini adaIah daerah berbukit, bergunung dan merupakan rawan bencana aIam tanah I0ngs0r dan banjir. Jumlah penduduk Desa Sidorejo pada tahun 2018 sebanyak 4.828 jiwa. Desa ini termasuk daerah surplus karena tanahnya yang subur, dikarenakan abu vulkanik gunung berapi sehingga banyak tanaman yang tumbuh dengan baik. Potensi andalan daerah adalah di bidang pertanian dan holtikultura sedangkan komoditi andalan daerah adalah padi, jagung, dan ketela. Pada saat ini, penduduk desa Sidorejo memanfaatkan air bersih dari sumber air desa dan belum memiliki pelayanan air bersih yang memadai. Dikarenakan aliran air minum dari sumber air desa kurang memadai seringkali bermasalah hingga membawa lumut dan lumpur serta terkadang terputus jaringannya karena longsor maka warga desa Sidorejo memutuskan untuk membuat sarana penyediaan air bersih yang layak guna mengatasi masalah air bersih di desanya. Studi ini bertujuan untuk mengetahui kebutuhan air bersih yang dibutuhkan di desa Sidorejo, mengetahui perencanaan jaringan pipa dan mengetahui rencana anggaran biaya yang diperlukan. Sesuai k0ndisi lapangan dan t0p0I0gi daerah, jaringan air minum diaIirkan menggunakan sistem gravitasi yang terdiri dari bak penangkap air, bronkaptering, sampai pada pipa transmisi. Bak penangkap dirancang mengelilingi sumber air baku lebar 3.70 meter dan panjang 1.87 meter yang berfungsi untuk menampung air sumber sementara. Bronkaptering dibangun dengan dimensi Iebar 3,40 m dan tinggi 2 m diIengkapi sistem filter sederhana untuk menjaga kualitas air minum sebelum dialirkan menuju pipa transmisi. Jaringan transmisi dari broncaptering dialirkan menggunakan pipa GI dia 3” sepanjang 96 meter dan pipa PVC (RRJ) S 12,5 sepanjang 1.920 meter yang dilengkapi dengan thrust block disetiap 8 meter. Rencana Anggaran Biaya (RAB) yang dibutuhkan dalam perencanaan sarana penyediaan air bersih di Desa Sidorejo Kecamatan Doko secara keseluruhan sebesar Rp. 189.089.000,- (Seratus Delapan Puluh Juta Delapan Puluh Sembilan Rupiah) termasuk PPn. Kata kunci: jaringan air bersih, bak penangkap, broncaptering, filter sederhana, sistem gravitasi, jaringan transmisi, thrust block, rencana anggaran biaya.